1985
DOI: 10.1073/pnas.82.16.5310
|View full text |Cite
|
Sign up to set email alerts
|

Cloning and characterization of cDNAs encoding 2,3,7,8-tetrachlorodibenzo-p-dioxin-inducible rabbit mRNAs for cytochrome P-450 isozymes 4 and 6.

Abstract: Monoclonal antibodies toward rabbit liver cytochrome P-450 isozyme 6 (P-450 6) were used to identify several recombinant clones from a pBR322 cDNA library that express 13-lactamase-P-450 6 hybrid proteins. The nucleic acid sequence and predicted amino acid sequence of a rabbit P-450 6 cDNA shows a high degree of homology with rat P-450c and mouse P1-450. When used as a probe to rescreen the library, the P-450 6 cDNA hybridized to several heterologous classes of cDNAs. One such class was shown to encode. P-450 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
22
0

Year Published

1986
1986
2017
2017

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 48 publications
(23 citation statements)
references
References 31 publications
1
22
0
Order By: Relevance
“…However, 78% homology was exhibited toward the predicted amino acid sequence from the rabbit P-450 4 cDNA clone, which encoded 83% of the protein (2). Two base pair changes in our previous sequence of the rabbit P-450 4 cDNA (2) changes leucine-356 to an arginine and isoleucine-461 to a threonine.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…However, 78% homology was exhibited toward the predicted amino acid sequence from the rabbit P-450 4 cDNA clone, which encoded 83% of the protein (2). Two base pair changes in our previous sequence of the rabbit P-450 4 cDNA (2) changes leucine-356 to an arginine and isoleucine-461 to a threonine.…”
Section: Resultsmentioning
confidence: 99%
“…It has been proposed that in humans, the gene equivalent to the major CL41Bz2-dioxin-inducible form in rabbit, P-450 4, and its counterparts in mice and rats, P3-450 and P-450d, respectively, does not exist (9). However, our laboratory has shown by DNA sequence analysis of a 600-base-pair (bp) cDNA clone called hpP-450 4, which was identified by hybridization of a rabbit P-450 4 cDNA clone (2) to a human cDNA library, that the human equivalent to rabbit P-450 4 gene is expressed in human liver (11). Southern blot analysis also showed that the P-450 4 and P-450 6 (P1-450) mRNAs were encoded by separate genes.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Kimura et al, 1984;Okino et al, 1985;Quattrochi et al, 1985). Fish CYP1As share significant sequence similarity with both CYP1A1s and CYP1A2s (Morrison et al, 1995) and display a combination of catalytic functions characteristic of the mammalian isoforms (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…In humans, CYP1A1 and 1A2 share 80% amino acid seqence identity and are ~40% identical with CYP1B1 (98)(99)(100)(101). cDNA clones and amino acid sequences of former two enzymes have been characterized in 1985-1986 (98-100), while a human CYP1B1 cDNA clone and amino acid sequence were reported in 1994 (101).…”
Section: T Shimadamentioning
confidence: 99%